2021
DOI: 10.3889/oamjms.2021.6250
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Death Caused by Severe-Critical COVID-19 in Jakarta: Case Series

Abstract: BACKGROUND: As of January 2021, Indonesia had the 21st highest number of total COVID-19 cases and the 17th highest total deaths among all countries. COVID-19 infection in pregnant women seems to negatively affect both maternal and neonatal outcomes. CASE REPORT: We describe four cases of pregnant women confirmed with severe and critical COVID-19 that resulted in maternal death from November until December 2020. The first case was complicated with thrombocytopenia, her condition quickly deteriorated post-deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The maternal death group had a higher comorbidities and pregnancy complications compared to the survived group (Cardiac disease, acute kidney injury, co-infection, and anemia). Contrary to many reports, our study did not found an increased prevalence of hypertension/preeclampsia, obesity, and diabetes in maternal death groups [28][29][30][31][32][33][34]. Acute kidney injury is the comorbidities with the highest risk to maternal death (OR: 19.14), followed by cardiac disease, co-infection, and anemia.…”
Section: Discussioncontrasting
confidence: 99%
“…The maternal death group had a higher comorbidities and pregnancy complications compared to the survived group (Cardiac disease, acute kidney injury, co-infection, and anemia). Contrary to many reports, our study did not found an increased prevalence of hypertension/preeclampsia, obesity, and diabetes in maternal death groups [28][29][30][31][32][33][34]. Acute kidney injury is the comorbidities with the highest risk to maternal death (OR: 19.14), followed by cardiac disease, co-infection, and anemia.…”
Section: Discussioncontrasting
confidence: 99%
“…There was one article that mentioned the increased risk of intubation and severe pneumonia (D'Antonio et al, 2021) Three studies mentioned the comorbidities found in patients. Almost all of the pregnant women aged >35 years had comorbidity (Djusad et al, 2021;Kurniawati et al, 2022;Shams et al, 2022). The most common comorbidity found was obesity.…”
Section: Resultsmentioning
confidence: 99%
“…There was an increase in mortality in the AMA group compared with the non-AMA group. Two studies found that almost all maternal death in advanced-age mothers were complicated by preeclampsia (Djusad et al, 2021;Kurniawati et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations